KAJIAN KEAGAMAAN TERHADAP NARAPIDANA DI LAMBAGA PEMASYARAKATAN KELAS I BANDAR LAMPUNG - Reza Nur Arifa (An Natiq, 2022)
Prisoners are people who are imprisoned due to their actions that violate the law and are God's imperfect creations as well as social beings who need other people to live. Correctional institutions have the task of fostering prisoners, including guiding in religious studies so that when they are free, convicts can have the quality of piety to God Almighty and have good attitudes and behavior so that they can return to society. The problem taken in this paper is how the influence of religious guidance on prisoners in the process of religious studies at the Class I Penitentiary. This writing aims to determine the effect of religious studies on prisoners. This writing is to provide an overview and explanation of how religious studies are conducted on prisoners and add to the knowledge of sociology from a religious perspective. This research is included in the field research and is descriptive. Methods of data collection in this study using observation, interviews, and documentation. The results of this paper indicate the influence of religious guidance on prisoners. The influence is in the form of changes felt by inmates, including increasing the quality of piety to God Almighty, improving attitudes and behavior of prisoners, and solving problems experienced by inmates.